(untitled) (ModaPalavra e-periódico, 2016)
The commercial strategies of some companies clothing, currently proposes a reflection on the ideal model of clothing collections. Thus, this study, doctoral fruit in design, offers an analysis of the clothingcollections building on the emergence of the first collection, the definition of fashion collection in the literature and will continue until the current collections. As a contribution, presents two terms to sort the collections, as has been diagnosed in the study, according to peculiarities of each collection and favors the recognition of collections that were not present in the literature and thus were not considered collections.